PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO ANIMASI BERBANTUAN CANVA PEMBELAJARAN IPAS KELAS IV SDN 104266 PEMATANG SIJONAM - Meirani; Ahmad Laut Hasibuan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low student learning outcomes caused by the lack of varied learning media applied by teachers and the absence of media development implemented. Thus, this study intends to analyse the process, validity and effectiveness of the development of animated video learning media assisted by Canva learning IPAS class IV SDN 104266 Pematang Sijonam which adapts the 4D development model (Define, Design, Develop and Disseminate). The instruments used in this research are validation questionnaires, needs and test sheets. From the results of the development process, it appears that this research produces products in the form of animated video media that can be used in the IPAS learning process. Furthermore, validity is carried out which involves learning practitioners, material and media experts. The result of the validity is that the product is very valid with a validity percentage of 92.29% categorised as ‘very valid’ and suitable for use. Finally, conducting an effectiveness test to determine the effectiveness of the product developed by conducting pretests and postests, and the result is that the animated video learning media assisted by Canva in grade IV IPAS learning is effective in improving student learning outcomes with a value of 0.74 categorised as very effective. Thus, this research contributes greatly to the development of technology and IPAS learning in schools and is able to effectively improve student learning outcomes.